THE IMPACTS OF ENVIRONMENTAL PERFORMANCE AND ENVIRONMENTAL COST AND ALSO FOREIGN OWNERSHIP ON CORPORATE FINANCIAL PERFORMANCE AND CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AS INTERVENING VARIABLES (Empirical Study On Manufacturing Companies Registered at Indonesia Stock Exchange for period 2013-2017) - B2091171006, JOHAN (MAKSI UNTAN, 2019)
This research is intended to analyse the factors which have impacts towards Corporate Financial Performance and Corporate Social Responsibility Disclosure as intervening variables on manufacturing companies registered at Indonesia Stock Exchange for period 2013-2017. The result of the research shows that environmental performance and environmental cost have negative and significant impact, however they have positive and significant impact on corporate social responsibility disclosure, foreign ownership has positive and significant impact on corporate financial performance and corporate social responsibility disclosure. Corporate social responsibility disclosure can be an intervening variable as a result of environmental performance and environmental cost but it canâ€™t be an intervening variable as an impact of foreign ownership on corporate financial performance.Â Keywords : environmental performance, environmental cost, foreign ownership, corporate financial performance, corporate social responsibility disclosurDAFTAR PUSTAKAAbiodun, Y. & Babalola. (2012). The Impact Of Corporate Social Responsibility On Firmâ€™s Profitability In Nigeria. Volodymyr Dahl East Ukrainian National Unoversity, Ukraine.Â Al Sharairi, Jamal Adel. (2005). The Impact of Environmental Costs on the Competitive Advantage of Pharmaceutical Companies in Jordan. Middle Eastern Finance and Economics, ISSN: 1450-2889 Issue 15.Â Al-Tuwajiri, dan Sulaiman. (2004). The Relation Among Environmental Disclosure, Environmental Performance, dan Economic Performance: A Simultenaous Equation. Approach. Accounting Environment Journal.USA. 5-10.Â Angela. (2015). Pengaruh Kinerja Lingkungan Terhadap Kinerja Finansial Dengan Pengungkapan Corporate Social Responsibility (CSR) Sebagai Variabel Intervening, Universitas Sanata Dharma, Yogyakarta.Â Anggraini, R. D. Pengaruh Kepemilikan Institusional dan Kepemilikan Asing Terhadap Pengungkapan Pertanggungjawaban Sosial Perusahaan Dalam Annual Report (Studi Empiris pada Perusahaan Non Keuangan yang Tercatat di BEI Tahun 2008-2009), Universitas Diponegoro, Semarang.Â Angling. (2010). Environment Agency, Almondsbury, Aztec West.Â Apriyanti, D. & Januarti, I. (2005). Pengaruh Tanggung Jawab Sosial Perusahaan Terhadap Kinerja Keuangan, Universitas Diponegoro, Diponegoro.Â Arifah, D. A. & Jaâ€™Far, M. (2006). Pengaruh Dorongan Manajemen Lingkungan, Manajemen Lingkungan Proaktif dan Kinerja Lingkungan Terhadap Public Environmental Reporting, Universitas Isalam Sultan Agung, Semarang.Â Arndt M & Einhorn B. (2010). 50 Perusahaan Paling Inovatif. BloombergBusinessweek. Edisi bahasa Indonesia. No. 16. 3-9 Juni 2010. Hal. 10-16.Â Atmaja, A. A. & Wibowo, A. J. (2015). Pengaruh Kepemilikan Asing dan Corporate Social Responsibility Terhadap Kinerja Perusahaan yang Terdaftar dalam Indeks Sri-Kehati Tahun 2009-2013, Universitas Atma Jaya, Yogyakarta.Â  Bahri, S. & Cahyani, F. A. (2016). Pengaruh Kinerja Lingkungan Terhadap Corporate Financial Performance Dengan Corporate Social Responsibility Disclosure Sebagai Variabel Intervening (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI), STIE ASIA, Malang.Â Barkemeyer, R. (2007). Legitimacy As a Key Driver and Determinant of CSR in Developing Countries, University of St Andrews, Amsterdam.Â Bradshaw J., Keung A., & Rees G., Et Al. (2011). Children's Subjective Well-being: International Comparative Perspectives.Children and Youth Services Review.vol.33 no 4.Â Chariri & Ghozali. M (2007). Teori Akuntansi. Semarang: Badan Penerbit Universitas Diponegoro.Â Chhibber, P.K and Majumdar, S.K, (1999). Foreign Ownership and Profitability: Property Rights, Control and The Performance of Firms In Indian Industry. Journal of Law and Economics 46(3), 209-238.ISSN: 00222186Â Daniri, Mas Achmad. (2005). Reformasi Corporate Governance di Indonesia. Jurnal Hukum Bisnis.Â Darnall N. & B. Ytterhus (2005). Does a Facilityâ€™s Environmental Performance Predict its Financial Performance? Paper presented at the OECD/EPA/Environment Canada Conference on â€˜Public Environmental Policy and the Private Firmâ€™, June 14-15 2005.Â Djuitaningsih, T. & Ristiawatil, E. E. (2009). Pengaruh Kinerja Lingkungan dan Kepemilikan Asing Terhadap Kinerja Finansial Perusahaan, Universitas Bakrie, Universitas Jember.Â Dowling, J. & Pfeffer, J. (1975). Organisational Legitimacy: Social Values and Organisational Behavior, Pacijic Sociological.Â Freeman, R. Edward dan David L. Reed. (1983). â€Stockholders and Stakeholders: A New Perspective on Corporate Governance.â€ California Management Review. Vol. 25. No. 3. hlm. 88 â€“ 106.Â Gray, et. al. (1995). Corporate Social and Environmental Reporting: A Review of Literature and a Longitudinal Study of UK Disclosure. Accounting, Audiitng, and Accountability Journal, Vol.8 No 2: 47-76.Â Hadi, Nor. (2011). Corporate Social Responsibility. Yogyakarta : Graha IlmuÂ Hansen & Moven (2007). Akuntansi Manajemen, Edisi 7 Buku 2. Jakarta; Salemba Empat.Â Haryati, R. (2013). Pengaruh Corporate Social Responsibility, Kinerja Lingkungan dan Struktur Corporate Governance Terhadap Kinerja Keuangan Perusahaan Yang Terdaftar di Bursa Efek Indonesia, Universitas Diponegoro, Semarang.Â Hidayat, R. R, Zahroh, Rohelmy, F. A. (2015). Efektivitas Penerapan Biaya Lingkungan Dalam Upaya Meminimalkan Dampak Lingkungan, Universitas Brawijaya, Malang.Â Januarti, Indira, Apriyanti D (2005). Pengaruh Tanggung Jawab Sosial Perusahaan terhadap Kinerja Keuangan, Jurnal MAKSI.Jensen, Michael C. dan W.H. Meckling. (1976). Theory of The Firm: Managerial Behavior, Agency Cost and Ownership Structure. Journal of Financial Economics 3. Hal 305-360.Kaeokla, P. and Jaikengkit, A. (2013). â€œExploring the corporate social responsibility reporting: A case study in Thai Listed Companies,â€ Africian Journal of Bussiness Management, Vol. 7, No. 28, pp2794-2800Kartawijaya, T. M. & Aulia, S. (2013). Analisis Pengungkapan Triple Bottom Line dan Faktor yang Mempengaruhi Lintas Negara Indonesia dan Jepang, Universitas Indonesia, Jakarta.Li, Y. & Bewley, K. (2000). Disclosure Of Environmental Information By Canadian Manufacturing Companies: a Voluntary Disclosure Respevtive. Lindblom, C. (1994). The implications of organizational legitimacy for corporate social performance and disclosure. Paper presented at the Critical Perspectives on Accounting Conference, New York.Â Lindrianasari. (2007). Hubungan Antara Kinerja Lingkungan dan Kualitas Pengungkapan Lingkungan Dengan Kinerja Ekonomi Perusahaan di Indonesia, Universitas Lampung, Lampung.Â Mauliddina, S. (2018). Pengaruh Environmental Performance, ISO 14001, dan Environmental Cost Terhadap Kinerja Keuangan Perusahaan Manufaktur, Universitas Islam Negeri Syarif Hidayatullah, Jakarta.Â Molina-AzorÃn JF, Claver-CortÃ©s E, LÃ³pez-Gamero MD and TarÄ± JJ. GreenManagement and Financial Performance: A Literature Review. ManagementDecision. 2009. Vol. 47 No.7. pp. 1080-1100.Â Mustika, R. R. (2017). Pengaruh Environmental Performance, encironmental Cost dan CSR Disclosure Terhadap Financial Performance (Studi Kasus pada Perusahaan Manufaktur yang Terdapat Di BEI Periode 2013-2015), Universitas Dian Nuswantor, Semarang.Â Pramesti, G. (2014). Kupas Tuntas Data Penelitian dengan SPSS 22. Jakarta: PT. Elex Media Komputindo.Â Pujiasih. (2013). Pengaruh Kinerja Lingkungan Terhadap Kinerja Keuangan Dengan Corporate Social Responsibility Sebagai Variabel Intervening, Universitas Negeri Semarang. Semarang.Â Sarwono, J. (2017). Mengenal Prosedur-Prosedur Populer dalam SPSS 23. Jakarta: PT. Elex Media Komputindo.Â Shocker, A.D. dan Sethi, S.P. (1974). An Aprroach to Incorporating Social Preferences in Developing Corporate Action Strategies. Melville Publishing Company: Los AngelesÂ Suchman, M. C. (1995). Managing Legitimacy: Strategic And Institutional Approaches, University Of Wisconsin, Madison.Â Sudaryanto. (2011). Pengaruh Kinerja Lingkungan Terhadap Kinerja Finansial Perusahaan Dengan Corporate Social Responsibiity (CSR) Disclosure Sebagai Variabel Intervening, Universitas Diponegoro, Semarang.Â Sugiyono. (2017). Statiska Untuk Penelitian. Bandung: Alfabeta.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  (2018). Metode Penelitian Kuantitatif. Bandung: Alfabeta.Â Sujarweni, V. W. (2016). Kupas Tuntas Penelitian Akuntansi dengan SPSS. Yogyakarta: Pustaka Baru Press.Â Tamba, E. G. H. (2011). Pengaruh Struktur Kepemilikan Terhadap Pengungkapam Tanggung Jawab Sosial Perusahaan (Studi Empiris pada Perusahaan Manufakturing Secondary Sectors yang Listing di BEI tahun 2009), Universitas Diponegoro, Semarang.Â Rakhiemah, A. N. & Agustila, D. (2009). Pengaruh Kinerja Lingkungan Terhadap Corporate Social Responsibility (CSR) Disclosure dan Kinerja Finansial Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia, Universitas Airlangga, Surabaya.Â Wondabio, L. S. & Sayekti, Y. (2007). Pengaruh CSR Disclosure Terhadap Earning Response Coefficient, Unhas, Makassar.Â Xiau, X et al. (2004). Modeling Gross Primary Production Of Temperate Deciduous Broaddleaf Forest Using Satellite Image and Climate Data, Elsevier Inc.